The efficiency droop impact of GaN‐based LEDs on the performance of OFDM visible light communication system. Issue 5 (16th March 2016) - Lu, Huimin; Yu, Tongjun; Jia, Chuanyu; Zhang, Yini; Wang, Jianping; Zhang, Guoyi
Abstract: The physical mechanism in efficiency droop of GaN‐based LEDs fabricated by metal organic chemical vapor deposition (MOCVD) was investigated by experiment and calculation. On this basis, the efficiency droop impact on the performance of orthogonal frequency division multiplexing (OFDM) visible‐light communication (VLC) system was analyzed. The numerical results show that the VLC system performance decreases obviously under the impact of the LED efficiency droop. And, the performance deterioration of OFDM VLC system aggravates as FFT sampling rate increase due to signal dynamic range enlargement. Furthermore, the efficiency droop impact on the VLC performance can be alleviated by adjusting the LED operating condition. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)